Morphological and molecular characterization of Ptychodiscus noctiluca revealed the polyphyletic nature of the order Ptychodiscales (Dinophyceae). Issue 5 (24th August 2016) - Gómez, Fernando; Qiu, Dajun; Dodge, John D.; Lopes, Rubens M.; Lin, Senjie
Abstract : The planktonic dinoflagellate Ptychodiscus noctiluca combined distinctive morphological features such as a disk‐shaped anteroposteriorly compressed cell body and an apical carina, together with a flexible and tough cell covering, suggesting intermediate characteristics between thecate and naked dinoflagellates. Ptychodiscus noctiluca was examined by light, epifluorescence, and scanning electron microscopy from specimens collected in the Mediterranean Sea and the North and South Atlantic Ocean. Ptychodiscus noctiluca showed a straight apical groove that bisected the carina, a cell covering with a polygonal surface reticulum, nucleus without capsule, sulcal intrusion in the episome, sulcal ventral flange, and yellowish‐green chloroplasts that are shared characters with Brachidinium / Karenia . The cell division was the typical binary fission of gymnodinioid dinoflagellates, although exceptionally in an oblique transversal axis. We examined the intraspecific variability during incubation experiments. In the fattened cells, termed as Ptychodiscus carinatus, chloroplasts transformed into dark granules, and the cell acquired the swollen and smaller stage, termed as P. inflatus . Ptychodiscus carinatus, P. inflatus, and Diplocystis antarctica are synonyms of P. noctiluca . Molecular phylogeny based on the SSU rDNA sequence revealed that Ptychodiscus branched within the short‐branching dinokaryotic dinoflagellates as an independent lineage with affinity to Brachidinium/Karenia and Karlodinium / Takayama in a generally poorly resolved clade. Our results indicated that the order Ptychodiscales, established for unarmored dinoflagellates with a strongly developed pellicle, has artificially grouped thecate dinoflagellates ( Kolkwitziella, Herdmania ), naked dinoflagellates with thick cell covering ( Balechina, Cucumeridinium ) and other insufficiently known unarmored genera with typical cell coverings ( Brachidinium, Ceratoperidinium ).